Origin disputed. The making, use and evaluation of Ghanaian textiles - Malika Kraamer (Afrique Archéologie Arts, 2007)
Since the 1990s, heated debates have unfolded in Ghana on the origin of kente cloth. These discussions mainly concern the primacy of Asante versus Ewe weaving. Weaving has a long history in many parts of Ghana, and interconnections between textiles from the Ewe- and Twi-speaking regions go back at least to the 19th century.In this article, I will disentangle the ways in which different current claims on the origin of kente cloth are locally reproduced and understood, and therefore I will provide insights in local perceptions and constructions of the past. To unravel apparent paradoxes, I will focus my attention on different ways of seeing, experiencing, interpreting and performing the past in a field of contested narratives. Narratives not only create coherent scenarios which articulate shared meanings but are also further shaped in their fierce contestations over control and authority in interpreting the past correctly.